BUREAUCRACY REFORMS ON THE SYSTEM DIMENSIONS AND PROCEDURES IN KUPANG CITY GOVERNMENT INTEGRATED LICENSING SERVICES - William Djani (Universitas Sebelas Maret, 2015)
This aim of this paper is to propose solutions to the systems and procedures reform, as part of the bureaucratic reform, in the City of Kupang. Generally, Indonesian bureaucracy has undergone significant reform, which is the result of convergence between external and internal factors. Bureaucracy Reform of the bureaucracy can be classified into three groups: institutional reform, personnel resources reform and systems and procedures reform. In many cases, the failure of system and procedures reform has hindered the effectiveness of bureaucracy reform as a whole. Therefore getting insight on the government commitment to promote system and procedure reform is imperative. This study discusses Kupang City government commitment to reform the system and procedures. Keywords: Bureaucracy, System and Procedure Reform, Public Services.